Transitional justice from below : grassroots activism and the struggle for change - McEvoy, Kieran; McGregor, Lorna (Human rights law in perspective ;, 2008)
From vaguely exotic origins on the outer edges of political science, the study of 'justice' in times of transition has emerged as a central concern of scholarship and practical policy-making. This collection discusses the role of human rights in transition, the usefulness of perspectives from above, and the contested meanings of 'transition'.